Tinjauan Yuridis Tentang Peralihan Hak Atas Tanah dalam Objek Sengketa - Desi Handayani Simbolon; Isnaini Isnaini (Jurnal Ilmiah Penegakan Hukum, 2017)
Juridical Issues Regarding Transition of Land Rights in the Object of DisputesAbstractLand is a place for human settlements as well as a source of livelihood for those who make a living through agriculture and ultimately land is also the last place for people to die. The law regarding land in Indonesia is influenced by a colonial legal system. This is because for hundreds of years Indonesia was colonized by the Dutch, so that there are two kinds of land ownership, namely lands with western rights and lands with customary rights, of course different about the transition, in terms of buying and selling, also ways of legal protection and legal certainty for the land owner concerned. Transition of land rights is a legal action aimed at transferring rights from one party to another. When someone has transferred his rights (land rights), to someone else "legally" then that person has no more rights to the land that has been transferred since the transfer of rights. The purpose of this study was to find out the process of transferring land rights in the object of the dispute and to find out the judges' consideration in deciding on land rights cases. This type of research is normative ayuridis. The nature of this research is descriptive analytical.